The Education Character in Boarding Schools: Implementing Civic Learning to Develop Student Responsibility - Jennyta Caturiasari; Tiara Yogiarni; Indah Nurmahanani (CV. Creative Tugu Pena, 2025)
This study aims to examine the implementation of Civic Education (Pendidikan Kewarganegaraan or PKn) within the cultural environment of a boarding school to enhance students’ character development, particularly in terms of responsibility and discipline. Employing a qualitative approach with a case study method, the research focuses on a single boarding school as the primary subject. Data were collected through observations, in-depth interviews with teachers, students, and the principal, as well as document analysis. The findings reveal that Civic Education is not only delivered theoretically in the classroom but is also integrated into students’ daily lives through consistent habituation, school regulations, and exemplary behavior demonstrated by all members of the school community. The boarding school environment, which emphasizes discipline and independence, provides ample space for the internalization of character values, especially responsibility and discipline. These results indicate that a contextual approach to Civic Learning, embedded within a strong school culture, effectively reinforces character formation. Thus, the contextualized implementation of Civic Education in the cultural environment of a boarding school